The hidden cost of real time electricity pricing - Ioana Bejan; Carsten Lynge Jensen; Laura Mørch Andersen; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2019)
In theory real time pricing ensures more efficient electricity markets than time of use pricing. However, people are prone to habits and regularity, so real time pricing may impose a greater cost of reacting on consumers. In a randomized field experiment we compared the cost of reacting to incentives under these two pricing regimes. We utilized smart-metered hourly power consumption to unobtrusively measure treatment effects. We found that real time pricing reduces consumer surplus from reacting to incentives by half, compared to reacting under a corresponding time of use pricing regime. This suggests a substantial economic value to households of the regularity and predictability provided by time of use pricing.
Keywords: L51; L94; C93; Q41; 330; real time electricity pricing; time of use electricity pricing; field experiment; household cost of reacting